ANALISIS FAKTOR- FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA PEGAWAI BIDANG SUMBER DAYA AIR PADA DINAS PEKERJAAN UMUM KABUPATEN INDRAGIRI HULU - Iskandar, Yenny (Eko dan Bisnis: Riau Economic and Business Review, 2019)
This research was conducted at the Office Dinas Pekerjaan Umum of Kabupaten Indragiri Hulu, located on Jalan Raya Pematang Reba. This study aims to determine the causes of job satisfaction at the Office Dinas Pekerjaan Umum of KabupatenÂ  Indragiri Hulu. The purpose of the research that the author is doing is to find out the causes of factors that affect employee job satisfaction in the field of water resources (SDA), as well as to find out the efforts made in overcoming the factors that influence job satisfaction in the Department of Public Works water Office Dinas Pekerjaan Umum of Kabupaten Indragiri Hulu. In conducting this research the author uses interview and questionnaire methods in an effort to collect data. The author requires data relating to the problem under study. The types and sources of data used in this study are primary and secondary data. As for the population and sample in this study are all the number of employees working in the field of Water Resources Public Works Office Dinas Pekerjaan Umum of Kabupaten Indragiri Hulu. From the results of the research that the authors did, it can be seen that the factors that influence employee job satisfaction in the field of Water Resources Public Works Office Dinas Pekerjaan Umum of Kabupaten Indragiri Hulu are facilities and infrastructure, Compensation, and Work Environment. These factors influence job satisfaction in the field of Water Resources, Public Works Agency, Kabupaten Indragiri Hulu